The Platformization of Music - Eyre, Ramsay (The Columbia Journal of Law & the Arts, 2026)
The story of the twenty-first century music industry has been one of platformization. While musical records were formerly sold as discrete physical units, or alternatively heard on the radio, listeners’ primary mode of engagement with recorded music has become almost completely replaced by online streaming platforms, which offer access to entire catalogs of recorded music for a subscription fee or for free with advertisements. This Article argues that recorded music is now a platform industry. This transformation has had significant consequences. Long-standing problems in the music industry have been magnified, including determining fair compensation through the copyright system and the consolidation of copyright ownership in both recording and publishing. They have also been supplemented by new problems stemming from the platform model of distribution: discriminatory, opaque, and declining compensation for musicians; user surveillance; the discriminatory treatment of musicians through platform placement; and new implications for the heterogeneity of musical culture. Addressing the challenges of the music industry’s platformization will require adapting and applying tools from the law of networks, platforms, and utilities (“NPU”), including rate regulation, nondiscrimination rules, and structural separations. These policies, some of which already govern parts of the music industry but are limited in scope, could help counter the harmful effects of platform power in music. Public options and cooperative governance also provide promising avenues and may be preferable to the regulation of private streaming platforms alone. Viewing music streaming as a platform industry suggests well-established legal and policy tools that advocates can use to build a healthier and fairer system of commerce to support musical culture.